DIRECTION OF MORAL EDUCATION TEACHER TO ENRICH CHARACTER EDUCATION - Mohd Zailani Mohd Yusoff; Aswati Hamzah (SCAD Independent, 2015)
This paper discusses moral education which should begin by focussing on what exactly is meant by the term “moral human being” in Character Education. This is because whatever approach is used has to be based on the exact and clear understanding of the moral human being himself. A moral human being should posses the components categorised as concept, that is, the rules and principles which are deemed necessary to be used in actions and feelings or emotions which support the belief that a concept or action should be carried out. Apart from that, a moral human being should have the moral knowledge of the surroundings, know how to interact and act according to the decisions made. Character education will enable one to be a moral human being who should know the good, desire the good and do good.